Properties of Fiber-Matrix Interfaces of Natural Fiber Composites - Herrera-Franco, P. J.; Valadez-González, A.
In this article, an overview of the earlier efforts to characterize the properties of the natural fiber/matrix interphase and its relevance in the control of final effective properties of a composite material is given. Because of the increasing awareness of environmental issues, natural fibers have become important and there has been a renewed and ever growing interest in their use in the development of low cost "eco-friendly" natural fiber reinforced composites. Physical, chemical and mechanical properties of naturals fibers, obtained from different sources, such as leaves, bast, fruits as well as wood-flour, have been widely studied. Their incorporation as reinforcement in the manufacture of polymeric materials (thermoplastic, thermo setting, elastomeric and more recently, biodegradable, green composites)and cementitious matrix composite materials have resulted in a great amount of work to study the physico-chemical fiber and matrix interactions and the as well as the experimental micromechanical methods for Interphase characterization. A model system, namely, henequen fiber-HDPE matrix will be used to illustrate the importance of the fiber-matrix interphase modification, the physico-chemical interactions and their characterization as well as an attempt to optimize such interphase properties and the effect on laminate mechanical properties.
Keywords: ALKALINE TREATMENTS; BIODEGRADABLE BIOCOMPOSITES; CEMENTITIOUS COMPOSITES; CHEMICAL TREATMENTS; FIBER PULL-OUT; FIBER SURFACE TREATMENT; FIBER-MATRIX INTERPHASEINVERSE GAS CHROMATOGRAPHY (IGC); MICROMECHANICAL TECHNIQUES; NATURAL FIBERS; PHYSICAL TREATMENTS; SINGLE FIBER FRAGMENTATION TEST; THERMOPLASTIC POLYMERS; THERMOSETTING POLYMERSX-RAY PHOTOELECTRON SPECTROSCOPY (XPS)